Professionalism and technological pedagogical and content knowledge skills of primary school teacher - Siti Ni'matul Fitriyah; Eddy Sutadji; Radeni Sukma Indra Dewi (Research and Development in Education (RaDEn), 2025)
Teacher professionalism includes a deep understanding of content, pedagogical skills, and adaptiveness to student needs, which is in line with the TPACK framework that integrates content knowledge, pedagogy, and technology in teaching practice. This study aims to examine the relationship between the professionalism of teachers and Technological Pedagogical and Content Knowledge (TPACK) ability among elementary school teachers. The method used is mixed methods with a sequential explanatory design. Quantitative data were collected from 167 respondents and analyzed using multiple linear regression, while qualitative data were obtained from in-depth interviews with nine teachers and analyzed using the Miles and Huberman framework. The results of the quantitative analysis showed that the professionalism of the teachers (pedagogical, personality, social, and professional competencies) had a significant effect on teachers' TPACK skills. Qualitative analysis findings indicate that teachers exhibiting a strong commitment to professional standards and self-improvement are more adept at efficiently integrating technology into their instruction. This study emphasizes that improving teacher professionalism is key to strengthening TPACK capacity to support the success of education policies and the quality of learning.